(untitled) (London Journal of Research In Management & Business, 2024)
This paper focuses on the possibility of cross-border tourism projects between Jordan, Egypt and Saudi Arabia, with a focus on cooperative tourism tactics. The study presents a cross border tourism project model which describes the structure for analyzing and developing cross border tourism strategies. Cultural, historical, natural, and economic conditions are suggested to outline several project options: cultural and historical interactions based on common history, new opportunities in natural and health tourism, and the enhancement of economic cooperation. Thus, it is possible to state that these projects can positively affect the development of the tourism industry, preserve cultural and natural heritage, and contribute to the regional economic development. Thus, the study suggests that Jordan should include the cross-border tourism into its national plans and strategies, engage in diplomacy, create task forces, and obtain international funding and technical cooperation.